Produtividade, estabilidade e adaptabilidade em progênies de polinização aberta de Eucalyptus urophylla S.T. Blake - Pupin, Silvelise [UNESP]; De Araújo Dos Santos, Arielen Virgínea [UNESP]; Zaruma, Darlin Ulises Gonzalez [UNESP]; Miranda, Aline Cristina [UNESP]; Da Silva, Paulo Henrique Muller; Marino, Celso Luis [UNESP]; Sebbenn, Alexandre Magno; De Moraes, Mario Luiz Teixeira [UNESP] (My University, 2015)
Prediction of genetic gains within breeding programs is not always compatible with those observed in practice. One reason for this inconsistency is the lack of knowledge of genotype-environment interaction (GxE). The aim of this study was to estimate genetic variation, evaluate the GxE, investigate the genetic correlation between pairs of environments and for the set, and to study the productivity, stability and adaptability at 2 years of age for diameter at breast height (DBH) in five progenies trials of Eucalyptus urophylla, used in a randomized complete block design, with the number of progenies ranging from 138 to 167, four to eight blocks and five to six plants per plot. Estimates of variance components and genetic parameters were obtained using the REML/BLUP method. For analysis of productivity, stability and adaptability, the HMRPGV method was used. The highest DBH growth was observed in Anhembi (10.52 cm) and Uberaba (10.20 cm). Estimates considered high were obtained for the coefficient of individual additive genetic variation (>13.3%) and average heritability among progenies (>0.40), indicating the possibility of obtaining genetic gains by selection among progenies. The coefficient of determination of the GxE was 1.7%, a fact that led to a high value of genotypic correlation between the performance of the progenies and environments (78.1%), indicating that the interaction is simple. The first six progenies showed a coincidence of 100% in the order of stability (HMGV), adaptability (RPGV) and productivity (HMRPGV), being 13% higher than the overall mean of five experiments (9.21 cm). When ordering the progenies, the selection of the 20 best in growth led to an increase in gain ranging of from 10.4 to 70%. Anhembi is the ideal place to have a breeding population which will be good in the other places as well.
Productivity, stability and adaptability in open pollination progenies of Eucalyptus urophylla S.T. Blake
Keywords: Genotype x environment interaction; REML/BLUP; Tree breeding